(untitled) (American Journal of Technology and Applied Sciences, 2025)
Heat exchangers are a very important part of technological devices in the chemical industry and related fields. The share of heat exchangers in the oil and gas processing industry is 50%. This article is devoted to the study of the problem of formation of salt plugs in heat exchangers of the oil and gas industry